Gender digital divide and online participation: A cross-national analysis - Younghoon Chang; Mehri Shahzeidi; Hyerin Kim; Myeong-cheol Park (International Telecommunications Society (ITS), 2012)
To achieve the information society for all, access for all is crucial. However, many countries have reported to have large gender discrepancies in online access and participation. This study empirically verified user perception data and compared the data across countries and genders to determine the differences between countries and genders. The results of surveys in Cambodia, Iran, and Korea verify that each aspect of the digital divide and online participation has a different influence on each aspect of digital access and online participation between the genders in each country. In this study, we propose measurement items of digital access and user participation in the online context. This paper also offers guidelines for online policy and business strategy for targeting users with different levels of digital access.
Keywords: 330; Digital Divide; Gender Digital Divide; Access; Online Participation; Cross-national